Nuclear and cytoplasmic sites for anti-sense control. - Cornelissen, M (1989)
In transgenic tobacco, anti-sense control of the chimaeric bar (bialophos resistance) gene is manifested by a reduced bar transcript level and a reduced synthesis of bar translational product (PAT, phosphinothricin acetyl transferase) per transcript (1). This study shows that the anti-bar gene controls the transcript level and the translation efficiency of the bar mRNA through independent events and at different cellular sites. On the basis of these results a model for the mechanism of anti-sense control is proposed.